Supplementary Material for Extensive genetic differentiation between recently evolved sympatric Arctic charr morphs - Guðbrandsson, Jóhannes; Kapralova, Kalina H.; Franzdóttir, Sigríður R.; Bergsveinsdóttir, Þóra Margrét; Hafstað, Völundur; Jónsson, Zophonías O.; Sigurdur S. Snorrason; Palsson, Arnar (figshare, 2019)
Supplementary tables and figures